A Fourier-transform infrared study on the interaction between sulfoglycolipid and phosphatidylcholine. - Attar, Mayssa. (University of Ottawa (Canada), 1999)
The objective of this study was to investigate the interaction between the sulfoglycolipids, sulfogalactosylceramide (SGC) or sulfogalactosylglycerolipid (SGG), and dimyristoylphosphatidylcholine (DMPC) in a mixed model liposomal system (molar ratio 2:3). Structural and dynamic changes of the liposome contents were monitored by Fourier-transform infrared (FTIR) spectroscopy. Thermotropic FTIR analysis showed a single gel-to-liquid crystalline phase transition for SGC+DMPC liposomes (42$\sp\circ$C) and SGG+DMPC liposomes (28$\sp\circ$C). The thermotropic profile of SGG liposomes showed a pretransition followed by the main gel-to-liquid crystalline phase transition (45$\sp\circ$C). Spectral changes of the amide and ester C=O bands arising from the functional groups at the interfacial region indicated a reduced hydrogen bonding of these groups in the mixed liposomes. Pressure-tuning FTIR of mixed SGC+DMPC liposomes showed that the methylene chains of SGC and DMPC were more orientationally disordered than those of the individual lipid liposomes. Analysis of SGG symmetric and antisymmetric $\rm CH\sb2$ stretching bands in the gel phase and liquid crystalline phase revealed the insertion of DMPC into SGG bilayers results in an increase in the number of gauche conformers in the acyl chains as well as a greater number of conformational states. Overall, these results suggested that the mixed liposomes of sulfoglycolipid and phosphatidylcholine consisted of a homogeneous mixture in which mutual shielding reduced hydrogen bonding at the interfacial region, with a concurrent increase in the orientational and conformational disorder of the hydrocarbon chains.
Keywords: Chemistry, Biochemistry.